LA INTERPRETACIÓN JURÍDICA Y LOS CÁNONES INTERPRETATIVOS EN EL DERECHO CIVIL PERUANO - Araujo Morales, Cristian Javier (2022)
Law is a social-normative and linguistic phenomenon. For this reason it shares the characteristic of indeterminacy with language. The main manifestations of linguistic indeterminacy are ambiguity and vagueness, hence the need to resort to interpretation as the main tool for applying the Law. There are various theories on legal interpretation, as well as methods or interpretative canons to identify those interpretations that are valid, excluding arbitrary or irrational ones. In this article we have carried out a brief examination of the characteristic features of current law, the indeterminacy of law, legal interpretation and interpretive canons, as well as the main theories that have been proposed on the subject, to end by developing the interpretation criteria included in the Civil Code, in light of the doctrinal contributions found.